Phlegmasia Cerulea Dolens in the Upper Extremity: A Case Report and Systematic Review and Outcomes Analysis. (February 2016) - Greenberg, Jacques; Troutman, Douglas A.; Shubinets, Valeriy; Dougherty, Matthew J.; Calligaro, Keith D.
Phlegmasia cerulea dolens (PCD) is a rare form of venous gangrene that arises secondary to occlusion of venous outflow from a limb. Classically described in the lower extremity, it is rare in the upper extremity. We present a case report of upper extremity PCD and a systematic review with data analysis of 37 cases of PCD published in PubMed. Our analysis showed that concurrent lower extremity PCD was a statistically significant marker for worse outcomes in this patient population.